Democracy laid low by the market. (2nd September 2018) - Supiot, Alain
ABSTRACT: From its origins in antiquity to the emergence of neoliberalism, democracy had always been thought of as a fragile institutional construct, comprising two complementary dimensions: an objective dimension (its formal institutions), and a subjective one (instituting its citizens). Appeared in the 1970s, the Law and economic doctrine has undermined this bases of democracy by assimilating the enactment of laws to negotiation on a market, and reducing democracy to a 'market of ideas'. The specific status of speech in the democratic area fades out, paving the way for 'post-truth politics' and 'democratic dictatorships'.